A Comparison of the Problem-Solving Skills of Students in PJBL Versus CPJBL Model: An Experimental Study - Jalinus, Nizwardi; Syahril, Syahril; Nabawi, & Rahmat Azis (Journal of Technical Education and Training, 2019)
Each learning model has different pattern and approach that will affect the learning outcomes. Thus, a study is required focused on the effect of implementing the learning model so that it can become a reference for teachers. The study aimed to compare the students’ problem-solving skills using Project Based Learning (PjBL) model and Cooperative-Project Based Learning (CPjBL) model implementation. The study was carried using out a quasi-experiment method. To reveal problem-solving skills, students used the authentic Assessment technique. A t-test was used to analyse data. The results of the study showed that there is a significant difference in students’ problem-solving skills between the PjBL and the CPjBL model, and that these differences are strongly influenced by the syntax or stages of the instructional model. Results show that CPjBL is more effective to improve students’ problem-solving skills. In PjBL model, learning activities are directed to project assignment, while in CPjBL model, learning activities of students began with motivation to achieve the learning outcomes, which were provided by modules through cooperative learning, understanding the concept and work principles through instructional media, prototype, discussion and demonstration. The cooperative learning made students group learning more structured corresponded with learning topic assigned. The students group would continue to carry out project assignment with permanent members and learning topic. The CPjBL model is more superior than PjBL model in accordance with the ability of the students as the syntax of the model is systematically organized based on learning hierarchy.